2015
DOI: 10.1039/c5sc01208b
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule antagonists of cell-surface heparan sulfate and heparin–protein interactions

Abstract: A series of rationally designed surfen analogs were synthesized and utilized as antagonists of glycosaminoglycan–protein interactions, including the neutralization of the anticoagulant activity of fondaparinux, a synthetic pentasaccharide analog of heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Despite the low abundance of these phospho‐RTKs, surfen also caused a reduction in their phosphorylation. VEGF is known to interact with HS and surfen has previously been reported to inhibit VEGF‐mediated endothelial sprouting . Quantitative phosphoproteomics studies of Ext1 −/− endothelial cells similarly revealed that antagonism of HS inhibits phosphorylation of these RTKs .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite the low abundance of these phospho‐RTKs, surfen also caused a reduction in their phosphorylation. VEGF is known to interact with HS and surfen has previously been reported to inhibit VEGF‐mediated endothelial sprouting . Quantitative phosphoproteomics studies of Ext1 −/− endothelial cells similarly revealed that antagonism of HS inhibits phosphorylation of these RTKs .…”
Section: Resultsmentioning
confidence: 96%
“…For instance, surfen, an aminoquinoline with heparinneutralizing properties, was first reported in 1938 [32]. Since its discovery, surfen has been shown to inhibit HIV infection [33], vasculogenesis [34], or modulate T-cell activation [35], through the antagonism of HS GAG interactions with signaling and receptor proteins [36,37]. In this study, we report that surfen effectively and reversibly restricts mESCs in their pluripotent state by attenuating the activity of their surface GAG structures in growth factor association and signaling.…”
Section: Introductionmentioning
confidence: 99%
“…A structure-activity relationship was established by measuring the inhibition of HS-dependent FGF binding to CHO cells. 118 In addition, their activity as inhibitors of HS binding to receptor for advanced glycation endproducts (RAGE) in vitro and neutralization of the anticoagulant activity of unfractionated heparin and low molecular weight heparins were investigated. The dimeric molecular structure of surfen and its aminoquinoline ring systems were found to be essential for its interaction with HS.…”
Section: Targeting Heparan Sulfate-protein Interactionsmentioning
confidence: 99%
“…Dimeric analogs displayed higher inhibitory potency than surfen and blocked downstream FGF signaling in mouse embryonic fibroblast cells. 118 Importantly, oxalyl surfen ( 26 ) was shown to neutralize both in vitro and in mice the synthetic heparin analog fondaparinux, for which no antidote exists. 118 These findings illustrate the therapeutic potential of small molecules as antagonists of HS and raise the possibility of using surfen-type compounds as biochemical tools and as potential effectors in disorders that involve GAG-protein interactions.…”
Section: Targeting Heparan Sulfate-protein Interactionsmentioning
confidence: 99%
“…[11] Unfortunately,the number of small molecules able to tune the heparin action is quite limited. [12] This is due to the chemical peculiarities of heparin (highly negative charge density,p olydispersity) in addition to its conformational flexibility, [13] which have made the molecular recognition of heparin and the rational design of synthetic ligands very challenging tasks. [14] We envisioned that dynamic covalent chemistry [15] could help in the discovery of specific ligands for intrinsically heterogeneous and elusive biomolecular targets.…”
mentioning
confidence: 99%